2016
DOI: 10.1103/physrevb.94.094104
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nitride frameworks and dense crystalline polymorphs

Abstract: We used ab initio random structure searching (AIRSS) to investigate polymorphism in C3N4 carbon nitride as a function of pressure. Our calculations reveal new framework structures, including a particularly stable chiral polymorph of space group P 43212 containing mixed sp 2 and sp 3 -bonding, that we have produced experimentally and recovered to ambient conditions. As pressure is increased a sequence of structures with fully sp 3 -bonded C atoms and three-fold coordinated N atoms is predicted, culminating in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 73 publications
5
49
0
Order By: Relevance
“…These observations may suggest that the Pharaoh's serpent material has a structure based on triazine (C 3 N 3 ) rings linked via bridging -N=, along with some -NH-units, as found in the g-C 3 N 4 , TGCN, and PTI structures, with the possibility that some three-dimensional linking might occur to form polymeric units as predicted by theoretical studies. [18,19,21] However, the 13 C chemical shifts observed for our Pharaoh's serpent materials also match closely with those observed for structures based on linked heptazine (tri-s-triazine, C 6 N 7 ) units, including Liebig's melon, melem (triamino-s-heptazine), and other substituted molecular heptazine complexes. [11,39,43,44] Lotsch et al [11] reported two signal groups with peak maxima at 164 and 157 ppm for Liebig's melon [11] ( Figure S6, Supporting Information).…”
Section: Articlesupporting
confidence: 79%
See 1 more Smart Citation
“…These observations may suggest that the Pharaoh's serpent material has a structure based on triazine (C 3 N 3 ) rings linked via bridging -N=, along with some -NH-units, as found in the g-C 3 N 4 , TGCN, and PTI structures, with the possibility that some three-dimensional linking might occur to form polymeric units as predicted by theoretical studies. [18,19,21] However, the 13 C chemical shifts observed for our Pharaoh's serpent materials also match closely with those observed for structures based on linked heptazine (tri-s-triazine, C 6 N 7 ) units, including Liebig's melon, melem (triamino-s-heptazine), and other substituted molecular heptazine complexes. [11,39,43,44] Lotsch et al [11] reported two signal groups with peak maxima at 164 and 157 ppm for Liebig's melon [11] ( Figure S6, Supporting Information).…”
Section: Articlesupporting
confidence: 79%
“…[13,[15][16][17] Interestingly, it has also been predicted that open framework varieties containing mixed sp 2 as well as sp 3 bonded units could exist. [18][19][20][21] Most carbon nitride materials under current investigation are produced by thermolytic condensation reactions of organic molecular precursors such as dicyandiamide (DCDA, C 2 N 4 H 4 ) and melamine [C 3 N 3 (NH 2 ) 3 ], giving rise to a range of polymeric C x N y H z compounds. [22] However, Liebig's initial syntheses of "melon" formed part of a series of studies involving reactions of thiocyanate compounds, including NH 4 SCN and KSCN treated with Cl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, TGCN samples were exposed to high pressure and high temperature conditions in a diamond anvil cell, and new crystalline peaks appeared indicating formation of a new type of C 3 N 4 framework consisting of triazine rings linked by sp 3 -bonded C atoms, corresponding to structures predicted by ab initio searching techniques. 60,61 Such open framework structures have been suggested to be energetically competitive with the graphitic layered compounds, and they could in fact be present within the amorphous materials produced by thermolysis and other reactions at ambient pressure.…”
Section: Triazine-based G-c 3 N 4 Structuresmentioning
confidence: 99%
“…Later theoretical studies then predicted the likely existence of various triazine-based g-C 3 N 4 polymorphs based on different stacking arrangements of the graphitic sheets, so that stacking disorder might be present within the experimental samples. 60,61 Algara-Siller et al were first to report forming bulk crystalline TGCN as a product of condensation reactions involving DCDA in molten salt (LiCl/KCl eutectic mixture) media. 23,62 The TGCN compound became deposited as a film on the walls of the glass vessel or at the surface of the molten salt reaction medium.…”
Section: Triazine-based G-c 3 N 4 Structuresmentioning
confidence: 99%
“…Liu [ 1 ], Cohen [ 2 ], and further theoretical studies [ 3 , 4 , 5 , 6 ] predicted that saturated sp 3 -hybridized carbon nitride compounds have a bulk modulus comparable to or larger than that of diamond. Since then, the synthesis of low-compressible C 3 N 4 forms has been the main goal of studies related to superhard materials science [ 7 ].…”
Section: Introductionmentioning
confidence: 99%